What are the view of Irish birth parents and foster carers on post adoption contact - Donovan, Bernadette (Public Health and Primary Care, 2008)
The purpose of this study is to explore the views of Irish foster carers and birth parent' views on the issue of post adoption contact. Post adoption contact is the level of contact that children who have been adopted from care have with their birth families. The study aims to give the reader an enhanced understanding of adoption and post adoption contact. The objective of the study is to inform future HSE policy development on post adoption contact with birth and extended families for children who have been adopted from long term care.
Keywords: Adoption in Ireland; Foster care